PERAN REMAJA DALAM PENANAMAN NILAI-NILAI KEAGAMAAN ( Studi kasus Masjid Baiturrohman Desa Beji Kecamatan Junrejo Kota Batu ) - Muhammad Alfikri Syah Reza; Chalimatus Sa’dijah; Mutiara Sari Dewi (VICRATINA, 2020)
The condition of adolescents and the community around the Baiturrohman mosque in Beji Village, Batu City is very far from positive, it becomes a challenge for REMAS Baiturrohman to invite their kindness to positive activities. The purpose of this study is to describe the mosque youth program activities in the inculcation of religious values, describe the implementation of the program activities in inculcating religious values, and describe the effectiveness of the mosque youth activity program in inculcating religious values. To achieve these objectives, this research was conducted with a qualitative approach to the type of case study research, data collection procedures carried out using the observation method, interviews by asking questions related to the problem to be studied, and documentation. Data Analyst Techniques are data reduction, data presentation, conclusion. Checking the validity of the findings by persevering observation, triangulation, and peer testing. the role of mosque youth in inculcating religious values in the Baiturrohman Mosque has been going well in line with the programs determined through several programs of the Sunday morning religious study group, madarasah diniyah education, and the maulid rosul assembly, with the implementation of each program consisting of the values of worship, morals, and creed.